The key success factors to adopting lean practices : the case of South American manufacturing firms (2023)
Purpose The purpose of this paper is to identify the factors that promote the successful adoption of lean practices in manufacturing firms operating in developing economies in South America. Design/methodology/approach Based on the results obtained from